Tropical Climate Less Affects Covid19 Transmission than Population Density: Perspective of Indonesia - Anwar Rovik; Anggi Pratama; Ayu Rahayu (Jurnal Kesehatan Lingkungan, 2022)
Introduction: Indonesia is ranked the 4th most populous country in the world. Since Covid19 is highly transmissible from human to human, Indonesia might suffer a long period of the Covid19 pandemic than other less-populous countries. This study aimed to find the correlations of tropical climate, population density and confounding factors with Covid19 progression in Indonesia from March to August 2020. Methods: The climatological data, population density, laboratory testing, and the confirmed Covid19 cases were statistically analyzed. The correlations between each data were performed with Pearson’s Correlation Coefficient using a Statistical Package for the Social Sciences. The values of statistical significance were considered at 95% and 99% confidence intervals. Results and Discussion: Indonesia recorded more than 1,315 confirmed Covid19 cases in almost all provinces (30 out of 34) during the dry season (March to August 2020). During the early pandemic, DKI Jakarta and East Java have been the epicenters of the pandemic in Indonesia. Humidity and precipitation have a weak negative correlation, while the temperatures have a weak positive correlation. Population density and laboratory testing have a strong positive and significant correlation with the cumulative confirmed Covid19 cases. Conclusion: Our study indicates that tropical climate less affects the cumulative Covid19 case in Indonesia than population density and laboratory testing capacity.